Leprosy Fiqh Rules: A Jurisprudence Comparative - Yassin Al-Obaidi, Saddam Hussein (Journal of Tikrit University for Humanities, 2023)
Leprosy is a common and well-known disease since antiquity. Some jurisprudential rulings related to it were contained in some ancient fiqh books, although those rulings were very few. This research came to show the rule of establishing the choice of the spouses in the annulment of marriage with lepers, the presence and witnesses of the leper for Friday and congregational prayers, and Imama in prayer.